1989
DOI: 10.1021/ac00188a018
|View full text |Cite
|
Sign up to set email alerts
|

Permselectivity and ion-exchange properties of Eastman-AQ polymers on glassy carbon electrodes

Abstract: Eastman-AQ55D is a new poly(ester sulfonic acid) cation exchanger available in a commercial dissolved form. Films of this polymer were coated onto glassy carbon surfaces, and the resulting electrodes exhibit attractive permselectivity, ion-exchange, and antifouling properties. Substantial improvement in the selectivity is observed as a result of excluding anionic species from the surface. The charge-selective behavior is demonstrated in the presence of a variety of compounds of neurological significance. A rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 10 publications
3
51
0
1
Order By: Relevance
“…Polymeric coating has proved to be one feasible technique for this purpose. [1][2][3][4][5][6][7][8] However, polymer-coated electrodes appear to have a limited number of applications, 2,7 with the exception of stripping analysis of trace metals. [3][4][5][6]8 This may be due to slow mass transport of organic analytes in the membrane.…”
mentioning
confidence: 99%
“…Polymeric coating has proved to be one feasible technique for this purpose. [1][2][3][4][5][6][7][8] However, polymer-coated electrodes appear to have a limited number of applications, 2,7 with the exception of stripping analysis of trace metals. [3][4][5][6]8 This may be due to slow mass transport of organic analytes in the membrane.…”
mentioning
confidence: 99%
“…Electrode 5 is likely to resist protein adsorption with efficiency comparable to or slightly less than GC electrodes coated with membranes such as a basehydrolyzed cellulosic film 2 or poly(ester sulfonic acid) 7 , 638 ANALYTICAL SCIENCES JULY 1999, VOL. 15 and much more effectively than a GC electrode modified with p-carboxymethylphenyl group.…”
Section: Reusability and Electrochemical Performance Of Electrodementioning
confidence: 99%
“…To circumvent this problem, there have been many efforts to develop modification methods that would increase surface hydrophilicity and thus decrease protein adsorption. Coating with membranes such as cellulose acetate 1 , a base-hydrolyzed cellulosic film 2,3 , Nafion 4,5 , or poly(ester sulfonic acid) [6][7][8] has proven to be a feasible technique for this purpose. However, membranecoated electrodes seem to have found only a few applications 2,7 , except in stripping analysis of trace metals [3][4][5][6]8 , probably due to the slow mass transport of organic analytes in thick and well-packed polymeric membranes.…”
mentioning
confidence: 99%
“…A layer for discriminating oxygen or hydrogen peroxide from the electrochemical interferences is strongly desired to develop a sensing system. [1][2][3][4][5][6] Recently, we have reported that the porous and hydrophobic properties of a poly(dimethylsiloxane) (PDMS) layer are suitable for restricting hydrophilic interferences and hydrogen peroxide, while allowing permeating gases, such as oxygen 7 and nitric oxide 8,9 selectively. The permeability of several electroactive species through a PDMS layer on the electrode has been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%